Soil Organic Carbon Stocks and Spatial Variability in Urban Green Spaces: Insights from the Kalyan–Dombivli Municipal Corporation, Mumbai Metropolitan Region, India - Madhuri Wani; D.M. Mahajan; Deepavali Shirurkar (Journal of the Indian Society of Soil Science, 2026)
within the Kalyan–Dombivli Municipal Corporation (KDMC) in the Mumbai Metropolitan Region, India. A total of 102 composite soil samples were collected from 30 ward groups representing residential, agricultural, and mixed land-use zones at two depths (0–15 cm and 15–30 cm). Laboratory and geospatial analyses quantified SOC distribution, depth-wise variation, and land-use influence. Results revealed high mean SOC concentrations (≈10.9%) and substantial average carbon stocks (~404 t C ha-1 within 0–30 cm). Surface soils exhibited slightly higher SOC than sub-surface layers, though the latter contributed nearly half of the total carbon pool, indicating deep carbon stabilization. Spatial mapping identified distinct carbon “hotspots” (>450 t C ha-1) in vegetated residential and institutional areas such as Kala Lake and Titwala, whereas disturbed and compacted peri-urban zones recorded lower stocks (